Faktor yang Berpengaruh terhadap Kelulusan Uji Kompetensi Mahasiswa Prodi D3 Kebidanan STIKes MERCUBAKTIJAYA Padang - Widya Lestari; Dian Febrida Sari; Desi Wildayani (FORIKES, 2021)
Competency test is a method to evaluate cognitive, affective and psychomotor abilities of health workers. This study aims to analyze the factors that influence the passing of the competency test of the D3 Midwifery Study Program students at STIKes MERCUBAKTIJAYA, Padang. The design of this study was cross-sectional. Respondents were 187 Indonesian Midwife Competency Test participants in the first taker route from the D3 Midwifery Study Program at STIKes MERCUBAKTIJAYA Padang in 2018 who were selected by purposive sampling technique. Data were collected through documentation study, then analyzed by Chi square test and independent samples t-test. The results showed that there was a relationship between passing the competency test try out and passing the competency test, and there was no relationship between the attendance of competency test debriefing and passing the competency test. Keywords: midwifery students; competence test; graduation ABSTRAK Uji kompetensi merupakan metode untuk mengevaluasi kemampuan kognitif, afektif dan psikomotor tenaga kesehatan. Penelitian ini bertujuan untuk menganalisis faktor-faktor yang mempengaruhi kelulusan uji kompetensi mahasiswa Program Studi D3 Kebidanan STIKes MERCUBAKTIJAYA, Padang. Desain penelitian ini adalah cross-sectional. Responden adalah 187 peserta Uji Kompetensi Bidan Indonesia jalur first taker dari Program Studi D3 Kebidanan STIKes MERCUBAKTIJAYA Padang tahun 2018 yang dipilih dengan teknik purposive sampling. Data dikumpulkan melalui studi dokumentasi, lalu dianalisis dengan uji Chi square dan independent samples t-test. Hasil penelitian menunjukkan bahwa ada hubungan antara kelulusan try out uji kompetensi dengan kelulusan uji kompetensi, dan tidak ada hubungan antara kehadiran pembekalan uji kompetensi dengan kelulusan uji kompetensi. Kata kunci: mahasiswa kebidanan; uji kompetensi; kelulusan